Europe's Covid-19 outliers: German, Austrian and Swiss policy responses during the early stages of the 2020 pandemic. Issue 4 (December 2020) - Desson, Zachary; Lambertz, Lisa; Peters, Jan Willem; Falkenbach, Michelle; Kauer, Lukas
Highlights: Germany, Austria and Switzerland implemented effective policy to contain Covid-19. Contact tracing technology relies on effective and flexible governance. Federalism in Switzerland, Austria and Germany proved flexible during Covid-19. Germany, Austria and Switzerland had lower mortality and impact from Covid-19. Economic policies from Covid-19 will take years to fully evaluate. Abstract: Objectives: This paper presents an overview of the policy responses in Germany, Austria and Switzerland (the DACH region) during the early stages of the 2020 Covid-19 pandemic (Feb.-June 2020), which provides the context for a comparative policy analysis. This analysis provides insight into the possible implications of the policy actions taken in the region. Methods: An in-depth review and analysis of available data from the DACH countries was conducted. Data was collected from official government sources whenever possible, and supplemented by information from international databases and local reports. The data was then analyzed to identify common patterns as well as significant divergences across the DACH region, especially in the area of health policy and technology use. Results: The DACH countries faced similar epidemiological situations during the Covid-19 pandemic, and were largely successful at preventing many of the negative impacts seen across the rest of Europe. Although many differences in health systems and governance structures existed, the policy responses in all three countries managed to address some of the most important factors in containing an infectious disease outbreak of this magnitude. Conclusions: The actions taken by all three DACH countries appear to have been largely successful in reducing the health impact of Covid-19, allowing a return to normal economic activities much earlier than in neighboring countries. However, the implications of certain policies related to economic resilience and health system capacity cannot yet be fully evaluated and may even prove to have negative impacts into the future.